Pengaruh Servant Leadership dan Kualitas Kehidupan Kerja Terhadap Organizational Citizenship Behavior (OCB) dengan Kepuasan Kerja Sebagai Variabel Intervening pada Dinas Pendidikan Kota Padang - Revina Fatril; Ramdani Bayu Putra; Rindy Cira Dewi; Hasmaynelis Fitri (Journal of Law and Economics, 2022)
The purpose of this study was to determine how big the influence of Servant Leadership and Quality of Work Life on Organizational Citizenship Behavior (OCB) with Job Satisfaction as an Intervening Variable at the Padang City Education Office. Methods of data analysis using a questionnaire, with a sample of 34 respondents. The data analysis method used is multiple linear regression analysis and path analysis. Based on the results of the study, it showed that Servant Leadership and Quality of Work Life had a positive and significant effect on Organizational Citizenship Behavior (OCB) with Job Satisfaction as an Intervening Variable. Contribution of Servant Leadership and Quality of Work Life to Organizational Citizenship Behavior (OCB) With Job Satisfaction as Intervening Variable has an effect of 69.3% while the remaining 30.7% is influenced by other variables outside this study. Based on the results of this study, it is expected that the Company's Management can improve Organizational Citizenship Behavior (OCB) by increasing Servant Leadership, Quality of Work Life and Job Satisfaction at the Padang City Education Office through each indicator.